2017
DOI: 10.1016/j.triboint.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Tribological assessment of coated piston ring-cylinder liner contacts under bio-oil lubricated conditions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…EN coatings are deposited on specimens of dimension 6 mm diameter and 30 mm length for the tribological tests. Whereas for characterization purposes, coatings are deposited on blocks of dimension 15 Â 15Â2 mm 3 . The specimens are initially cleaned thoroughly using soap water and running water.…”
Section: Coating Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…EN coatings are deposited on specimens of dimension 6 mm diameter and 30 mm length for the tribological tests. Whereas for characterization purposes, coatings are deposited on blocks of dimension 15 Â 15Â2 mm 3 . The specimens are initially cleaned thoroughly using soap water and running water.…”
Section: Coating Depositionmentioning
confidence: 99%
“…Electroless nickel (EN) coatings show excellent corrosion resistance, anti-wear, and anti-friction properties. [2][3][4][5] The properties of EN coatings can be suitably tailored to cater into the industrial needs by varying the bath components, 6 heat treatment, 7 alloying with elements such as W, Mo, Cu, etc., [8][9][10] and co-deposition of composite micro/nano particles such as Al 2 O 3 , TiO 2 , SiC, PTFE, etc. 11 With the challenging industrial demands and aggressive environment, the development of high temperature self-lubricating coatings has gained immense importance.…”
Section: Introductionmentioning
confidence: 99%
“…Persson [12] said that the mix of particles with water is highly viscous and then lubricates more the tire/road interface. The lubricating action of particles mixed with lubricants has been observed in other tribosystems like piston ring-cylinder liner pairs in internal combustion engines [13][14] [15]. These authors have shown that adding additives like molybdenum disulfide [13] [14] or graphite [15] in oils helps to reduce friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…The lubricating action of particles mixed with lubricants has been observed in other tribosystems like piston ring-cylinder liner pairs in internal combustion engines [13][14] [15]. These authors have shown that adding additives like molybdenum disulfide [13] [14] or graphite [15] in oils helps to reduce friction and wear. Xu and coauthors in [15] attributed this performance to the higher viscosity of oil with additives (an esterified bio-oil has been used) compared with pure oil.…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, the main consideration for the application of texture is the influence of related parameters, and different texture parameters are designed for different application scenarios. For example, in Xu et al's [32][33][34][35][36] research, the application of different texture parameters in cylinders was studied, and friction and wear tests were carried out on the textured elements using a friction and wear machine. e research results provided a good understanding for the lubrication mechanisms of different textured surfaces.…”
Section: Introductionmentioning
confidence: 99%